PENGARUH MEDIA DAKON MATEMATIKA TERHADAP HASIL BELAJAR MATEMATIKA SISWA MATERI PENJUMLAHAN - Nor Asyriah; Siti Munawarah; Noor Fitriah (MEGA: Jurnal Pendidikan Matematika, 2022)
Islamic Elementary School Students/Elementary school Students need concrete objects in learning process, especially in learning mathematics. An interesting learning media makes students easy in understanding materials. However, there are many teachers still use conventional and traditional media such as textbooks. Teachers should modified the media to suit the this modern era. This study aims to determine the learning outcome of the first-grade students in MIN 3 Tapin using Dakon mathematics media. This study uses quantitative approach and a one group pretest-posttest design. The population in this study were all students in MIN 3 Tapin by total 184 people and the sample was the first-grade students in MIN 3 Tapin. Data collection techniques using test, interviews and documentation. Data analysis technique using t-test. The result shows that there as a significant influence between Dakon mathematics media and students learning outcomes. This is evidenced by the result of the t-test, namely t-count was 1,46 and t-table was 2,306. It’s found that t-count was 11,46 >t-table was 2,306 or t-count higher than t-table, its meant that H0 was rejected and H1 was accepted.